1958
DOI: 10.4039/ent9023-1
|View full text |Cite
|
Sign up to set email alerts
|

Life-histories and Habits of the Clover Mite, Bryobia praetiosa Koch, and the Brown Mite, B. arborea M. & A., in British Columbia (Acarina: Tetranychidae)

Abstract: Bryobia praetiosa Koch (1836) was formerly regarded as a complex of closely related species or races similar in morphological characters but varying widely in life-history, host plant specificity, and habits. The authors (30) have recently shown that two species, the clover mite, B. praetiosa Koch, and the brown mite, B. arborea Morgan and Anderson, can be distinguished in British Columbia on the basis of morphological characters. This paper presents ecological data in support of the morphological evidence. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
6

Year Published

1963
1963
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
2
14
0
6
Order By: Relevance
“…These observations on the role of predators in the present study support the view by CHANT (1959) or ANDERSON and MORGAN (1958) which have been demonstrated to be effective in stabilizing natural, tetranychid populations (eg. HOYT, 1969;FLAHERTY and HUFFAKER, 1970;FLAHERTY and HoY, 1971), whereas also in some other species there seems to be some circumstanc[al evidences which imply their effectiveness in the field (see HUFFAKER, et al, 1970).…”
Section: Discussionsupporting
confidence: 92%
“…These observations on the role of predators in the present study support the view by CHANT (1959) or ANDERSON and MORGAN (1958) which have been demonstrated to be effective in stabilizing natural, tetranychid populations (eg. HOYT, 1969;FLAHERTY and HUFFAKER, 1970;FLAHERTY and HoY, 1971), whereas also in some other species there seems to be some circumstanc[al evidences which imply their effectiveness in the field (see HUFFAKER, et al, 1970).…”
Section: Discussionsupporting
confidence: 92%
“…The discovery of multiple cryptic Bryobia species has implications for the management of these mites in broadacre agriculture, because species differ in their biology and ecology (Mathys 1957, Anderson and Morgan 1958, Helle and Sabelis 1985, and control strategies need to be devised separately for each species. The presence of cryptic species complicating management strategies has been shown within the Penthaleus species complex.…”
Section: Discussionmentioning
confidence: 99%
“…Similar variation between years has been documented in past studies involving Bryobia spp. and was attributed to varying weather conditions (Anderson 1958). Abundance of other arthropods did not show any significant differences in response to irrigation treatment.…”
Section: Resultsmentioning
confidence: 97%